(untitled) (REMUNOM, 2026)
The organization of disease prevention and control policies in Brazil follows the evolution of immunization actions and health surveillance within the SUS (Unified Health System). This research aimed to analyze the historical milestones of disease prevention and control policies in Brazil, from the evolution of the National Immunization Program (PNI) to the consolidation of health surveillance. To this end, a qualitative, descriptive, and exploratory study was conducted, developed through a narrative literature review. The search was carried out in the PubMed/MEDLINE, SciELO, and Virtual Health Library databases, in addition to official documents from the Ministry of Health. It was observed that over time, prevention actions ceased to be sporadic and became integrated into the routines of health services. The creation of the PNI organized vaccination throughout the country, expanded access, and contributed to reducing preventable diseases. With the SUS, immunization began to interact directly with health surveillance, allowing for data monitoring, identification of areas with low coverage, and guidance for more targeted interventions. The presence of Primary Care proved central to this process, especially due to direct contact with the population and continuous monitoring in the territory. These factors help explain differences in vaccination coverage between regions and reinforce the need for actions closer to the local reality. It is concluded that the effectiveness of policies depends on the articulation between immunization, surveillance, organization of services and health communication.